Germany's colonial pasts - Ames, Eric, 1969-; Klotz, Marcia, 1961-; Wildenthal, Lora, 1965- (Texts and contexts (Unnumbered), 2005)
'Germany's Colonial Pasts' is a wide-ranging study of German colonialism and its legacies.